ANALISIS KEGIATAN EKSTRAKURIKULER MEMBATIK TERHADAP KEMAMPUAN MEMBATIK SENI RUPA SISWA SEKOLAH DASAR DI DESA MANTINGAN, KECAMATAN JAKEN, KABUPATEN PATI - Rizky Alfiana; Djariyo Djariyo; Filia Prima Artharina (Universitas Muria Kudus, 2017)
This research is describe the analysis of batik extracurricular activities to the ability of batik painting of elementary school students in Mantingan Village, Jaken Sub-district, Pati Regency. This research uses qualitative descriptive approach with principal subject, extracurricular batik trainer, and students of SD N Mantingan. The object of this study is the analysis of batik extracurricular activities on the ability of art batik. Data collection is done by observation, interview. The data analysis techniques include data collection, data reduction, data presentation, and conclusion. To test the validity of the data used persistence. Batik extracurricular activities that have been implemented in SD N Mantingan have a role on the ability of batik art to produce various works of batik art. The ability of batik art, among others, elements and principles of art are taught by trainers or teachers able to make students can be creative, work, develop creativity, express feelings, talents, motivation and independence.